Introduction of Keris; an ancient weapon from Asian peninsula - Yogi Meranggi (Bali Tourism Journal, 2019)
Out of many weapons possessed by myriad inhabitant tribes of southeast Asia, Keris is probably the most unique and well known. The dagger is a common weapon along the Malayan Peninsula, Indonesia, and the Philippines. Keris can be classified into two types based on its shape, namely straight Keris and Luk (wavy) Keris, which always odd in number. Empu, the name given to the Keris maker, hardened iron as the core material in making the knife with particular techniques passed from their predecessor. An object can be classified as a Keris if it has fulfilled the strict prerequisite of Keris. Today’s society put Keris as heritage that should be preserved. Its function progressed from the weapon into antiques, part of the traditional ceremony or even considered as a sacred relic by in Balinese communities. In addition, Keris is also hunted by collectors who put interest on it. The weapon was made throughout a long and challenging process. To keep its durability from the natural oxidation process, therefore, the Keris owner is compulsory to do regular cleaning to preserve its shine and durability.